Value-based marketing : marketing strategies for corporate growth and shareholder value - Doyle, Peter, 1943-2003. (Chichester, England ; Hoboken, NJ : John Wiley & Sons, 2008)
"This is the second edition of Value-Based Marketing. As with the first edition, it makes a powerful case for marketing's role in an organisation's success by establishing it on a sound intellectual basis. It answers critics of marketing who claim that it has not had the impact on management that its importance merits because of unclear objectives and weak intellectual foundations." "This book emphasises marketing's contribution to long-term shareholder value creation, which is the governing objective of management today. It explores, at both the strategic and tactical level, how this affects marketing planning, decisions about brands, pricing, communications and distribution." "For marketing professionals, the book provides a clear practical introduction to shareholder value analysis. It gives them the tools to develop the marketing strategies that will create the most value for the business."
"For top management and CFOs, the book explains how marketing generates shareholder value. It shows how top management should evaluate strategies and stimulate more effective and relevant marketing in their companies. Where relevant, case studies and illustrations have been updated."--Jacket
pt. I. Principles of Value Creation -- 1. Marketing and Shareholder Value -- 2. The Shareholder Value Approach -- 3. The Marketing Value Driver -- 4. The Growth Imperative -- pt. II. Developing High-Value Strategies -- 5. Strategic Position Assessment -- 6. Value-Based Marketing Strategy -- pt. III. Implementing High-Value Strategies -- 7. Building Brands -- 8. Pricing for Value -- 9. Value-Based Communications -- 10. Value-Based Marketing in the Digital Age.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Marketing -- Management; Corporations -- Valuation; Marketing -- Gestion; x; BUSINESS & ECONOMICS -- Marketing -- General; BUSINESS & ECONOMICS -- Distribution; Corporations -- Valuation; Marketing -- Management; Marketing; Shareholder-Value-Analyse; Wertorientiertes Management